Expression of the voltage-gated chloride channel ClC-2 in rod bipolar cells of the rat retina. - Enz, Ralf; et al. (Journal of Neuroscience, 1999)
Voltage-gated chloride channels (ClC) are highly conserved during evolution and appear to participate in a variety of physiological functions. Recently, ClC-2 was proposed to play a role in stabilizing the chloride equilibrium potential near or below the resting membrane potential in neurons expressing ligand-gated chloride channels. Because rod bipolar cells in mammalian retina express three forms of inhibitory ligand-gated chloride channels, we decided to study ClC-2 localization and function in the rat retina. RNA encoding ClC-1, -2, -3, -4, and -5 was detected by reverse transcription-PCR in the rat retina. ClC-2-specific antibodies identified protein on cell bodies and in synaptic layers. Double-immunofluorescence staining revealed that intense ClC-2 immunoreactivity colocalized with PKC- stained rod bipolar cells. Patch-clamp experiments performed with individual rod bipolar cells demonstrated the presence of a time-dependent, inwardly rectified current activated at hyperpolarizing membrane potentials. This current demonstrated selectivity for different anions (Cl- > l- > gluconate), was inhibited by Cd2+, and was minimally reduced by 4,4'- diisothiocyanatostilbene-2,2'-disulphonic acid. These features are consistent with currents generated by ClC-2 channels. Our data indicate that functional ClC-2 channels are present in retinal rod bipolar cells and support a role for ClC-2 in maintaining Cl- homeostasis in neurons with ligand-gated chloride channels.
UnivIS-Import:2017-12-18:Pub.1999.med.IB.profes_1.expres
Keywords: ClC; CNS; GABA receptor; Ligand-gated ion channel; Retina; Rod bipolar cell; Voltage-gated chloride channel